The infectivity of virus particles from Wolbachia-infected Drosophila - Angelique Asselin; Karyn Johnson (BMC Microbiology)
Abstract Viruses transmitted by arthropods pose a huge risk to human health. Wolbachia is an endosymbiotic bacterium that infects various arthropods and can block the viral replication cycle of several medically important viruses. As such, it has been successfully implemented in vector control strategies against mosquito-borne diseases, including Dengue virus. Whilst the mechanisms behind Wolbachia-mediated viral blocking are not fully characterised, it was recently shown that viruses grown in the presence of Wolbachia in some Dipteran cell cultures are less infectious than those grown in the absence of Wolbachia. Here, we investigate the breadth of this mechanism by determining if Wolbachia reduces infectivity in a different system at a different scale. To do this, we looked at Wolbachia’s impact on insect viruses from two diverse virus families within the whole organism Drosophila melanogaster. Drosophila C virus (DCV; Family Dicistroviridae) and Flock House virus (FHV; Famliy Nodaviridae) were grown in adult D. melanogaster flies with and without Wolbachia strain wMelPop. Measures of the physical characteristics, infectivity, pathogenicity, and replicative properties of progeny virus particles did not identify any impact of Wolbachia on either DCV or FHV. Therefore, there was no evidence that changes in infectivity contribute to Wolbachia-mediated viral blocking in this system. Overall, this is consistent with growing evidence that the mechanisms behind Wolbachia viral blocking are dependent on the unique tripartite interactions occurring between the host, the Wolbachia strain, and the infecting virus.